Cody

# Problem 59. Pattern matching

Solution 2015068

Submitted on 12 Nov 2019 by Asif Newaz
This solution is locked. To view this solution, you need to provide a solution of the same size or smaller.

### Test Suite

Test Status Code Input and Output
1   Pass
a = [0 1 1 0 -1 1 0 1 0 1 1 0 -1 1 0 1 0 1 0 0 -1 1 0 1 1 2 2 1 0 2 1 2]; b = [2 4]; out = matchPattern(a); assert(isequal(out(:), b(:)))

c = 1 c = 1 0 c = 1 0 -1 c = 1 0 -1 -1 c = 1 0 -1 -1 2 c = 1 0 -1 -1 2 -1 c = 1 0 -1 -1 2 -1 1 d = 1 0 -1 -1 1 -1 1 e = 1 e = 1 0 e = 1 0 -1 e = 1 0 -1 -1 e = 1 0 -1 -1 2 e = 1 0 -1 -1 2 -1 e = 1 0 -1 -1 2 -1 1 f = 1 0 -1 -1 1 -1 1 e = 1 0 -1 -1 2 -1 1 e = 1 -1 -1 -1 2 -1 1 e = 1 -1 0 -1 2 -1 1 e = 1 -1 0 -1 2 -1 1 e = 1 -1 0 -1 2 -1 1 e = 1 -1 0 -1 2 -1 1 e = 1 -1 0 -1 2 -1 1 f = 1 -1 0 -1 1 -1 1 e = 1 -1 0 -1 2 -1 1 e = 1 0 0 -1 2 -1 1 e = 1 0 -1 -1 2 -1 1 e = 1 0 -1 -1 2 -1 1 e = 1 0 -1 -1 2 -1 1 e = 1 0 -1 -1 2 -1 1 e = 1 0 -1 -1 2 -1 1 f = 1 0 -1 -1 1 -1 1

2   Pass
a = [0 1 2 3 4 5 6 7 1 2 3 4 5 6 7 8 0 2 3 4 5 7 8 0 0 0 2 3 4 5 6 7]; b = [2]; out = matchPattern(a); assert(isequal(out(:), b(:)))

c = 1 c = 1 1 c = 1 1 1 c = 1 1 1 1 c = 1 1 1 1 1 c = 1 1 1 1 1 1 c = 1 1 1 1 1 1 1 d = 1 1 1 1 1 1 1 e = 1 e = 1 1 e = 1 1 1 e = 1 1 1 1 e = 1 1 1 1 1 e = 1 1 1 1 1 1 e = 1 1 1 1 1 1 1 f = 1 1 1 1 1 1 1 e = 2 1 1 1 1 1 1 e = 2 1 1 1 1 1 1 e = 2 1 1 1 1 1 1 e = 2 1 1 1 1 1 1 e = 2 1 1 1 2 1 1 e = 2 1 1 1 2 1 1 e = 2 1 1 1 2 1 -8 f = 1 1 1 1 1 1 -1 e = 0 1 1 1 2 1 -8 e = 0 2 1 1 2 1 -8 e = 0 2 1 1 2 1 -8 e = 0 2 1 1 2 1 -8 e = 0 2 1 1 1 1 -8 e = 0 2 1 1 1 1 -8 e = 0 2 1 1 1 1 1 f = 0 1 1 1 1 1 1

3   Pass
a = [0 0 2 3 4 5 6 7 1 2 3 4 5 6 7 8 0 2 3 4 5 7 8 0 0 0 2 3 4 5 6 7]; b = [4]; out = matchPattern(a); assert(isequal(out(:), b(:)))

c = 0 c = 0 2 c = 0 2 1 c = 0 2 1 1 c = 0 2 1 1 1 c = 0 2 1 1 1 1 c = 0 2 1 1 1 1 1 d = 0 1 1 1 1 1 1 e = 1 e = 1 1 e = 1 1 1 e = 1 1 1 1 e = 1 1 1 1 1 e = 1 1 1 1 1 1 e = 1 1 1 1 1 1 1 f = 1 1 1 1 1 1 1 e = 2 1 1 1 1 1 1 e = 2 1 1 1 1 1 1 e = 2 1 1 1 1 1 1 e = 2 1 1 1 1 1 1 e = 2 1 1 1 2 1 1 e = 2 1 1 1 2 1 1 e = 2 1 1 1 2 1 -8 f = 1 1 1 1 1 1 -1 e = 0 1 1 1 2 1 -8 e = 0 2 1 1 2 1 -8 e = 0 2 1 1 2 1 -8 e = 0 2 1 1 2 1 -8 e = 0 2 1 1 1 1 -8 e = 0 2 1 1 1 1 -8 e = 0 2 1 1 1 1 1 f = 0 1 1 1 1 1 1

4   Pass
a = [0 0 2 3 4 5 6 7 1 2 3 4 5 6 7 8 0 2 3 4 5 7 8 0 0 0 12 13 140 150 160 1700]; b = [4]; out = matchPattern(a); assert(isequal(out(:), b(:)))

c = 0 c = 0 2 c = 0 2 1 c = 0 2 1 1 c = 0 2 1 1 1 c = 0 2 1 1 1 1 c = 0 2 1 1 1 1 1 d = 0 1 1 1 1 1 1 e = 1 e = 1 1 e = 1 1 1 e = 1 1 1 1 e = 1 1 1 1 1 e = 1 1 1 1 1 1 e = 1 1 1 1 1 1 1 f = 1 1 1 1 1 1 1 e = 2 1 1 1 1 1 1 e = 2 1 1 1 1 1 1 e = 2 1 1 1 1 1 1 e = 2 1 1 1 1 1 1 e = 2 1 1 1 2 1 1 e = 2 1 1 1 2 1 1 e = 2 1 1 1 2 1 -8 f = 1 1 1 1 1 1 -1 e = 0 1 1 1 2 1 -8 e = 0 12 1 1 2 1 -8 e = 0 12 1 1 2 1 -8 e = 0 12 1 127 2 1 -8 e = 0 12 1 127 10 1 -8 e = 0 12 1 127 10 10 -8 e = 0 12 1 127 10 10 1540 f = 0 1 1 1 1 1 1

5   Pass
a = [0 1 1 0 1 2 3 4 1 5 5 3 2 3 4 5 6 7 7 9 -4 -1 -1 -12 5 6 9 10]; b = [3 6]; out = matchPattern(a); assert(isequal(out(:), b(:)))

c = 1 c = 1 0 c = 1 0 -1 d = 1 0 -1 e = 1 e = 1 1 e = 1 1 1 f = 1 1 1 e = 4 1 1 e = 4 0 1 e = 4 0 -2 f = 1 0 -1 e = 1 0 -2 e = 1 1 -2 e = 1 1 1 f = 1 1 1 e = 1 1 1 e = 1 0 1 e = 1 0 2 f = 1 0 1 e = 3 0 2 e = 3 0 2 e = 3 0 -11 f = 1 0 -1 e = 1 0 -11 e = 1 3 -11 e = 1 3 1 f = 1 1 1